1974
DOI: 10.1073/pnas.71.2.329
|View full text |Cite
|
Sign up to set email alerts
|

Size Distribution and Molecular Polarity of Newly Replicated DNA in Escherichia coli

Abstract: Newly synthesized DNA, in E. coli lysogenic for the phage X, was labeled by short pulses of [ In bacteria, at least some of the newly synthesized DNA appears as short chains (Okazaki fragments) that are subsequently joined to long molecules (1-3). Whether such discontinuous replication occurs on both strands or only on one is an open question. Evidence, recently reviewed by Klein and Bonhoeffer (4), has been introduced for both possibilities. In order to resolve this question, in the case of Escherichia coli r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

1974
1974
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…This interpretation was confirmed in polA mutants, deficient in DNA polymerase I (13)(14)(15) and with DNA ligase mutants (11,16,17). Not only was all DNA synthesized in LMW pieces in polA and ligA mutants, but it then stayed short for some time, indicating that both DNA polymerase I and DNA ligase are the maturation functions.…”
supporting
confidence: 51%
“…This interpretation was confirmed in polA mutants, deficient in DNA polymerase I (13)(14)(15) and with DNA ligase mutants (11,16,17). Not only was all DNA synthesized in LMW pieces in polA and ligA mutants, but it then stayed short for some time, indicating that both DNA polymerase I and DNA ligase are the maturation functions.…”
supporting
confidence: 51%
“…Several groups have reported that they never observe more than 50% of the acid precipitable radioactivity in the Okazaki peak (Painter & Schaefer, 1969;Hyodo et al, 1970Hyodo et al, , 1971Iyer & Lark, 1970;Eisenberg & Dernhardt, 1974;Francke & Hunter, 1974a;Friedman, 1974;Louarn & Bird, 1974). SOIDe of the reports are not convincing because pulse-times were so long that the percentage of the total acid precipitable radioactivity found in the Okazaki peak is probably misleadingly small (Hyodo et al, 1970;.…”
Section: Are Both Sides Nlade Discontinuously?mentioning
confidence: 82%
“…As I will point Qut in the Discussion section, this is not an easy question to resolve. It is made even more difficult by the fact that the 5'----,)l3' strand may be replicated more or less discontinuously depending on mutations (Lark, 1972;Louarn & Bird, 1974) or on other conditions affecting the rate of synthesis (Herrmann et al, 1972;Olivera & Bonhoeffer, 1972). …”
Section: Are Both Strands Made Discontinuously?mentioning
confidence: 99%
See 1 more Smart Citation
“…The direction of replication across a given locus may be determined from the strand preference of Okazaki fragments specific for the marker considered, a technique well suited to the case of X prophages (23). Strains carrying XTSK prophages at zcjlS2 or dif positions, with or without psrA* (Fig.…”
Section: Resultsmentioning
confidence: 99%